Investigação in silico e in vitro do efeito antiparasitário da droga febrifugina em Trypanosoma cruzi - Silva, Dyonatan Fonseca (Universidade Federal Rural do Semi-Árido, 2020)
Chagas disease is a trypanosomiasis caused by the Trypanosoma cruzi parasite that affects the entire American continent and has spread to Europe and Asia, causing several deaths a year, damage to the economy of the endemic country and infecting more and more people through transmission routes alternatives. Several alternatives to search for new drugs for the control of parasitic diseases have been sought in recent years and the repositioning of drugs combined with in silico studies has shown to be a promising strategy, as it allows to predict whether or not a given drug has potential biological activity. Due to the various biological similarities between T. cruzi and Leishmania sp., in silico studies with positive results involving the use of febrifugin (FFG) analogs against L. donovani's trypanothione reductase (TR) enzyme raised the hypothesis that perhaps the molecule natural could be able to exhibit antiparasitic activity in vitro and that could also be able to bind to the binding site of TR. For the in vitro test, T. cruzi parasites were cultured in LIT (Liver Infusion Tryptose) medium supplemented with 10% fetal bovine serum and 10 IU/ml of penicillin/streptomycin and kept at 28 ºC. Then, the treatment with FFG and the positive control with benzonidazole were applied, both in five concentrations (1 mM, 500 μM, 250 μM, 125 μM and 62.5 μM) and the negative control for each treatment. For in silico testing, the protein structure was used, recovered, cleaned of non-protein binders and subjected to docking with the FFG. For the molecular simulation, the isolated A chain of TR was used, the dimer without the FFG and the dimer linked to the FFG obtained in the docking. The in silico analyzes showed the existence of several stable conformations for the FFG docking box, the chosen one (-7.4 kcal / mol) being used for the simulation and resulted in a stable bonding in the binding site of the enzyme interface. Analyzes of the effect of FFG in vitro showed that it exerted antiparasitic activity at concentrations of 500 μM and 62.5 μM, but only after two days after treatment.
Monografia
Keywords: Dinâmica molecular; Mecanismo de ação; Viabilidade parasitária; Molecular dynamics; Mechanism of action; Parasitic viability; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA